The impact of financial globalization on financial markets - AZZAOUI, Amar; DAOUI, Kheira (Dirassat Journal Economic Issue, 2012)
Financial markets know many evolutions in their structures and performances; they produce creative tools of investment which form a factor of investors’ attraction (individuals and enterprises). Besides their crucial role in society, they represent an important channel of communication and through this later, working unities in national economy could satisfy their financial needs. Change and evolution that are occurring in the international economy lead to the emergence of new phenomena which are characterized by liberal markets and capital mobility between countries without restrictions. This phenomenon is called financial globalization which impacts on financial decisions, individuals and countries